Impacts of COVID-19 pandemic on the wastewater pathway into surface water: A review - Bandala, Erick R.; Kruger, Brittany R.; Cesarino, Ivana [UNESP]; Leao, Alcides L. [UNESP]; Wijesiri, Buddhi; Goonetilleke, Ashantha (Elsevier, 2021)
With global number of cases 106 million and death toll surpassing 2.3 million as of mid-February 2021, the COVID-19 pandemic is certainly one of the major threats that humankind have faced in modern history. As the scientific community navigates through the overwhelming avalanche of information on the multiple health impacts caused by the pandemic, new reports start to emerge on significant ancillary effects associated with the treatment of the virus. Besides the evident health impacts, other emerging impacts related to the COVID-19 pandemic, such as water-related impacts, merits in-depth investigation. This includes strategies for the identification of these impacts and technologies to mitigate them, and to prevent further impacts not only in water ecosystems, but also in relation to human health. This paper has critically reviewed currently available knowledge on the most significant potential impacts of the COVID-19 pandemic on the wastewater pathway into surface water, as well as technologies that may serve to counteract the major threats posed, key perspectives and challenges. Additionally, current knowledge gaps and potential directions for further research and development are identified. While the COVID-19 pandemic is an ongoing and rapidly evolving situation, compiling current knowledge of potential links between wastewater and surface water pathways as related to environmental impacts and relevant associated technologies, as presented in this review, is a critical step to guide future research in this area.
Keywords: Assessing environmental impact; COVID-19; Potential for surface water dispersion; SARS-CoV-2 pandemic; Wastewater presence